'I Think, You Think': Understanding the Importance of Self-Reflection to the Taking of Another Person's Perspective. (8th June 2017) - Gerace, Adam; Day, Andrew; Casey, Sharon; Mohr, Philip
Abstract : This article reviews current knowledge about how the tendency to reflect on personal experience is related to the tendency to take another's perspective. While it is well established that self-reflection leads to a greater understanding of one's own emotions, cognitions, and behaviours, the extent to which it is associated with understanding others is less well understood, despite the implications of this for the development of more effective interventions to improve empathy. The types of self-reflection that are used in clinical and psychotherapeutic interventions are used to illustrate the possibilities here, and ways in which clinicians may increase their own self-reflection are also considered.